Systematic Mapping of the Literature on Smells in Software Development Requirements - Castillo-Motta, Mayra-Alejandra; Dorado-Córdoba, Rubén-Darío; Pardo-Calvache, César-Jesús; Orozco-Garcés, Carlos-Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2023)
One of the activities responsible for the success of a software development project is the specification of requirements, whose purpose is to ensure that the wishes or needs of the client clearly and accurately represent what they expect. A clear and structured requirement specification process avoids reprocessing at later stages of the project life cycle, generating a benefit in terms of time estimation for new tasks, cost, and effort. In this sense, it is important to have mechanisms or techniques to identify and mitigate possible errors during the requirements specification. Software engineering proposes the term “smell”, which can be defined as a specific symptom that can generate defects in a requirement. The objective of this paper is to establish a broader state of knowledge on the smell identification and classification present during the requirements specification and their impact on the generation of a phenomenon known as requirements debt. This article presents the results obtained after carrying out a systematic mapping of the literature, describing the proposals, initiatives, results, technological tools, benefits and challenges of smell identification and management in the requirements-gathering stage during the software development solutions.